The acute effect of knee brace on the electromyography activity of lower limb muscles in individuals with genu valgus during walking - AmirAli Jafarnezhadgero; Farshad Ghorbanloo; Arefeh Mokhtari Malekabadi; Sadegh Ghasemi (مجله پزشکی دانشگاه علوم پزشکی تبریز, 2021)
Background: Different factors affect walking biomechanics disturb the postural control. Genu valgus is one of the most important lower limb malalignments that affects the postural control and disrupts the posture. The purpose of the present study was to investigate the acute effect of knee brace on the electromyography activity of lower limb muscles in individuals with genu valgus during walking. Methods: In this semi-experimental and a laboratory typ study,. 24 boys with genu valgum (20-30 years old) volunteered to participate in the study. The electrical activity of the selected muscles was recorded by an electromyography system during walking with and without knee brace. Paired t-test was used for statistical analysis at a significance level of 0.05. Results: There was a significant increase in electrical activity of the semitendinosus muscle during walking with knee brace compared to walking without it (p = 0.037, d = 0.89). The electrical activity of other lower limb muscles did not show any significant differences during acute use of knee brace (P >0.05). Conclusion: The semitendinosus muscle in individuals with genu valgus is weak. Therefore, significant increase in the electrical activity of the semitendinosus muscle during wearing of knee brace means delaying the fatigue and indicating improvement in the muscular function.